INKED NARRATIVES AND SYMBOLIC EXPRESSIONS IN INDIGENOUS TATTOO PRACTICES - Kamal, Vineeta; Alam, Shamsher (ShodhKosh: Journal of Visual and Performing Arts, 2025)
This study examines the historical and contemporary significance of tribal tattooing as a global cultural practice, employing a qualitative, descriptive research methodology grounded in scholarly literature and historical records. The research explores the origin of tribal tattoos, tracing their evolution through archaeological and anthropological evidence, and analyzes their spiritual, social, and cultural functions across diverse indigenous societies. The paper is organized into key sections that first outline the traditional meanings and symbolic functions of tribal tattoos, followed by examination of contemporary adaptations and transformations in tattooing practices. The analysis is framed using multiple theoretical perspectives, including symbolic interactionism, structuration theory, optimal distinctiveness theory, and social identity theory. These frameworks contextualize tribal tattoos as tools of communication, identity formation, health practices, expression of taboos, gender dynamics, and mechanisms of social cohesion. Additionally, the study offers a comprehensive overview of various tattooing techniques and methods employed across different indigenous cultures, highlighting both commonalities and distinctions. The culminating section critically addresses the decline and marginalization of tribal tattoo traditions situating these changes within the broader socio-cultural and global dynamics. The findings emphasize the importance of preserving indigenous tattoo practices as vital cultural heritage amidst increasing global homogenization and cultural commodification.